Awareness of digital footprint management in the new media amongst youth - Tengku Siti Meriam Tengku Wook,; Hazura Mohamed,; Siti Fadzilah Mat Noor,; Zurina Muda,; Intan Yusrina Zairon, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The industrial revolution creates a new era where everything can be accessed via the Internet. However, despite all the advantages, the new era of technology comes with disadvantages as well. Studies have shown that the youth category is the group that is a synonym to technology. Most of the youth nowadays enjoy using the features but lacked the information on the footprint of their Internet browsing history. When individuals engaged with the Internet, they generated a complex trail of these digital footprints that may include their various presentation of self, based on social profiles and comments, traces of their activities, interest, interaction and anything else they choose to share online. However, the extent to which netizens are aware that they are creating these tracks and traces and have some ability to manipulate and control them is unclear at present. Thus, the objective of this paper is to identify the level of awareness among youth about the digital footprint. The research started with a structured survey distributed to respondents as a data collection requirement for analysis. A quantitative research method is employed in this research. Survey was conducted to the three main areas namely urban, suburban and rural as a sample of the population. Results were presented in the form of description analysis with respondents demographic and perception of respondents based on digital footprint awareness.